Effects of amygdaloid and amygdaloid-hippocampal lesions on object recognition and spatial working memory in rats. - Aggleton, J; Blindt, H; Rawlins, J (1989)
Neurotoxic lesions of the amygdala did not affect the postoperative acquisition of a nonspatial test of object recognition (delayed nonmatching to sample) even when retention delays were increased from 0 s to 20 or 60 s, or when test stimuli were deliberately repeated within a session. Although these amygdaloid lesions did not alter forced-choice spatial alternation, they slightly increased neophobic responses to novel foods and environments. In contrast, combined amygdalohippocampal (A + H) lesions impaired performance on the object recognition task when the retention intervals were increased beyond 0 s and when test stimuli were repeated within a session. The A + H rats were also severely impaired on the spatial alternation task, and they showed reduced neophobia. Comparisons with a previous study show that damage to the amygdala or hippocampus does not affect object recognition, whereas A + H damage produces clear deficits.